Nanoscience and computational chemistry : research progress - Castro, E. A. (Eduardo Alberto) 1944-, editor; Haghi, A. K., editor; Mercader, Andrew G. (Toronto ; New Jersey : Apple Academic Press, 2014)
Includes bibliographical references and index